2021
DOI: 10.1155/2021/5698765
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Different Antiepileptic Drugs on Blood Ammonia and Homocysteine Levels in Children with Epilepsy

Abstract: In this study, we performed a study on 106 children with epilepsy who were treated with sodium valproate (the VPA group, n = 37), oxcarbazepine (the OXC group, n = 34), or levetiracetam (the LEV group, n = 35). In addition, the clinical data of epileptic children who were newly diagnosed in the same period without antiepileptic drug (AED) treatment (the untreated group, n = 35) and normal children who received physical examination in our hospital (the healthy group, n = 35) were selected as controls. We analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…However, it is still not clearly known whether Hcy levels elevate in response to epilepsy disorders, AEDs, a collective effect, and/ or other factors. Though it has further been found that sodium valproate, oxcarbazepine, and levetiracetam are all effective as the first-line choice for the treatment of epilepsy and that levetiracetam and oxcarbazepine show lower incidence of adverse effects and do not increase blood Hcy 12 , it is still confusing to interpret the alterations in Hcy in patients with epilepsy 14 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is still not clearly known whether Hcy levels elevate in response to epilepsy disorders, AEDs, a collective effect, and/ or other factors. Though it has further been found that sodium valproate, oxcarbazepine, and levetiracetam are all effective as the first-line choice for the treatment of epilepsy and that levetiracetam and oxcarbazepine show lower incidence of adverse effects and do not increase blood Hcy 12 , it is still confusing to interpret the alterations in Hcy in patients with epilepsy 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The free Hcy might be more harmful than the protein-bound Hcy3, though few studies have distinguished between the two forms of Hcy. Epilepsies showing a variety of alterations, including elevated levels of Hcy 11 and related disorders, are treated by long-term AEDs 12 . Some of those, e.g., phenytoin (PHT) and carbamazepine that are enzyme-inducing AEDs, may cause disorders with elevated blood levels of Hcy 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with older AEDs, these new AEDs are less likely to infuence hepatic enzymes [9] and are supposed to be less likely to disrupt Hcy metabolism [10]. In recent years, some case-control studies have been conducted to explore the correlation between Hcy and new AEDs [11][12][13][14][15][16][17][18][19][20]. In a case study, Sun et al argued that the new AEDS do not cause elevated blood ammonia and Hcy levels, so they have high drug safety.…”
Section: Introductionmentioning
confidence: 99%